Rekayasa Saluran Gas Buang Sepeda Motor Guna Mengurangi Pencemaran Udara - Ahmad Marabdi Siregar; C A Siregar (Fakultas Teknik UMSU, 2019)
Air pollution from motor vehicle exhaust emissions is increasing, so it is necessary to attempt to control its exhaust emissions. Given the dangers of exhaust emissions, efforts need to be made to control and reduce air pollution so that negative impacts on people and the environment can be reduced. One engineering technology as a manifestation of vehicle emission control is engineering and modification of the exhaust gas channel. Engineering and modification is expected to be able to make a tool that will be able and function to reduce the danger of exhaust gases. The researcher will conduct experiments and manufacture of tools and initial testing on one motorized vehicle to see and observe the composition of the exhaust gas produced from the exhaust. The elements to be observed are CO values, HC values, and CO2 values as comparative data. The tool that will be used to observe and see these elements is the Gas Analyzer tool. This tool is one instrument that is useful for measuring the portion and composition of a combined gas. From the results of testing and analysis obtained data on the exhaust emission test with an average engine speed of 500 rpm, and with the temperature of the exhaust tube 40 0C to 45 0C. After testing the standard exhaust model, then testing the engineering exhaust model which added 50 gr, 70 gr, and 90 gr scrap of stainless steel obtained the best conclusion to reduce and reduce the danger of exhaust emissions is engineered exhaust which added 70 gr scrap of stainless steel . And when compared to a standard exhaust, CO elements dropped to 71.09% and HC elements dropped to 48.26% and CO2 elements dropped to 66.35%.